Hydrothermal evolution of the morphology, molecular composition, and distribution of organic matter in CR (Renazzo‐type) chondrites. (28th January 2018) - Changela, Hitesh G.; Le Guillou, Corentin; Bernard, Sylvain; Brearley, Adrian J.
Abstract: The morphology, molecular composition, and distribution of organic matter (OM) were investigated in a suite of CR chondrites to better constrain its hydrothermal evolution. Multiple focused ion beam sections were extracted from the matrices of seven CR chondrites. Scanning transmission X‐ray microscopy and transmission electron microscopy reveal OM ubiquitously distributed across the CR matrices. OM mainly occurs as either discrete submicron rounded or irregularly shaped vein‐like particles. Two spectral populations of organic particles were identified by carbon K‐edge X‐ray absorption near edge structure (XANES): the most abundant one, similar to insoluble organic matter (IOM) residues, contains aromatic, carbonyl, and carboxylic groups. The second population is more aromatic‐rich and lacks a distinctive carbonyl peak. An additional, ubiquitous organic component occurs associated with amorphous silicates and phyllosilicates. Less aromatic but aliphatic‐ and carboxylic‐rich, this diffuse OM is interpreted as the result of the redistribution of organic compounds by aqueous fluids. The most altered CR1 GRO 95577 contains a more mature OM and highly aliphatic‐ and carboxylic‐rich diffuse OM. This evolution, from the CR2s to the CR1, is comparable to that of terrestrial gas shale maturation involving cracking reactions, releasing bitumen‐like, aliphatic‐, and carboxylic‐rich compounds, and aromatic residues. Our observations support the accretion of soluble OM and its later polymerization to IOM, as well as the maturation of IOM and its partial oxidation, releasing mobile compounds. The differences in GRO 95577 are clearly attributable to the hydrothermal episode(s), but the relative role of water and temperature on the evolution of OM remains elusive.